The changing nature of transactions activity and liquidity in UK commercial property - Jones, Colin; Livingstone, Nicola; Dunse, Neil (International Journal of Strategic Property Management, 2016)
This paper examines changing transactions activity and liquidity over thirty years in the UK. It reviews the multi-dimensional concept of liquidity analysis and demonstrates that it is not just a function of the time necessary to sell an asset, a typical real estate perspective. Instead liquidity is defined in terms of transactions activity. The paper then hypothesises that urban change and an increased information base has contributed to a more active management of real estate portfolios and increased liquidity. Superimposed on this long term trend it is also hypothesised that property cycles create rise and falls in liquidity. The empirical core quantifies the changing nature of liquidity and transactions activity over thirty years from 1981 based on the IPD database. It confirms the hypothesised substantial rise in liquidity but increasing variability in the level of transactions activity from one year to the next queries the cyclical liquidity hypothesis. This is supported by causality tests. Over the last two decades a short term opportunity driven real estate investment culture appears to have emerged stimulated by the increased churn of properties, partly the consequence of the pace of urban change. It has brought greater volatility to the commercial real estate market.First Publish Online: 14 Dec 2016